PEMANFAATAN EKSTRAK DAUN KEMANGI (OCIMUM SANCTUM) SEBAGAI REPELAN LALAT RUMAH (MUSCA DOMESTICA) - Barus, Linda; Sutopo, Agus (Politeknik Kesehatan Tanjung Karang, 2019)
House flies are the species that play the most role in public health problems, namely as a vector of disease transmission. Control of house flies is needed without polluting the environment. The alternative developed is the use of plants as vegetable pesticides. Basil leaves used as basil leaf extract are used as vegetable insecticides to control house flies (Musca domestica). This research is an experiment to see the ability of basil leaf extract as a bioinsecticide on the repulsion/repellency of house flies. This research is experimental and analyzed using a two-way ANOVA analysis. The study consisted of two factors, the first factor was the dose of basil leaf extract: 0%, 20%, 30%, dan 40%, and the second factor, the time of observation of the repelling power of house flies/repelan for 5 minutes, 10 minutes and 15 minutes. Statistical test results stated that basil leaf extract: dose 0% sig value 0,011<0,05, dose 20% sig value 0,178>0,05, dose 30% sig value 0,031<0,05 and dose 40% sig value 0,007<0,05, so that the dose of 0% has an effect for the observation time of 15 minutes, the dose of 20% does not affect the repelling/repelling power of house flies, for observations of 5, 10 and 15 minutes, the dose of 30% and the dose of 40% affects, for all time observations.